Knowledge and activities for the oncological prevention of women invited for mammography screening as part of the "Population program for early detection of breast cancer" - Tomaszewska, Katarzyna; Michna, Aneta (Journal of Education, Health and Sport, 2019)
Breast cancer is a disease most often affecting women in the modern world and a huge challenge for modern medicine. "Breast cancer is not a sentence" - such statement is presented by one of the authors of the book position used in this paper. However, considering statistical data, every tenth woman asks herself whether this statement is true due to the highest percentage of cases of this disease among females. There may be many reasons for this situation, but one should also look at them in the lack of awareness of women about breast cancer prevention. Preventive actions are of considerable importance. They allow real recognition of the problem and implementation of activities aimed at reducing the risk of disease. Undoubtedly, some people are not aware of the seriousness of this situation, and the second part wonders what the reason for such a high percentage of cases is. The answer is simple - women do not perform self-examination of breasts, do not participate in preventive examinations and report to the doctor when the cancer process is already advanced. Aim of this paper The aim of this paper was to evaluate knowledge and activities for oncological prevention of women invited for mammography screening as part of the "Population program for early detection of breast cancer". Material and methods The study covered 105 randomly selected women in rural and urban areas of the Podkarpackie Voivodeship aged 50-69 covered by the "Population program for the early detection of breast cancer. The research was conducted in the period from 09/01/2017 to 10/31/2017. The author’s questionnaire consisting of 32 questions was used for the research. The research was voluntary and anonymous.For the purpose of this work, the following tests were used for questions on nominal scales for verification of hypotheses: V Kramer (2x3 tables, 4x5 etc.), Phi (2x2 tables) - these are symmetric measures based on chi-square test informing about the strength of dependencies between variables in cross tables. For questions on ordinal scales, Tb - Kendall or Tc tests were used - the first for 2x2 tables, the second 2x3, 4x5 tables, etc. The statistical analysis was carried out using the SPSS program and all relationships are statistically significant when p<0.05. Results and conclusions Knowledge and activities for the oncological prevention of women invited for mammography screening under the "Population program for early detection of breast cancer" is low. The source of knowledge about breast cancer is mainly media and leaflets. Women mostly know the main causes and symptoms of breast cancer. Over 70% of respondents say that they know the rules for conducting breast self-examination, but less than half of these women carry them out. Most of the women - 66.7% say that they know the rules of taking mammography, but half of them took part in the program. The most common reason for not using the invitation to study was the lack of time. According to the surveyed women, it appears that this is a program useful to fight cancer only in 36.5%. However, almost every woman was in favor of publicizing the problem in social media.